PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN INDUSTRI TERASI DI KABUPATEN SUMENEP - Alvin Arifin (Departemen Manajemen, 2020)
This study examines the influence of organizational culture and work environment on job satisfaction and employee performance. The object of the study was conducted in the shrimp paste industry in Sumenep Regency. This research is quantitative. The saturated sample used in this study is that the entire population is the research sample. The data collection method uses a questionnaire distributed to employees of the shrimp paste industry in Sumenep Regency. Data analysis uses Structural Equation Modeling (SEM) analysis using SmartPLS software. The results of the study that organizational culture positively and directly affect employee performance, but do not have an indirect effect through job satisfaction. The work environment does not have a significant direct effect on employee performance, but gives a positive and significant indirect effect through job satisfaction.